Characteristics of pediatric rhabdomyolysis and the associated risk factors for acute kidney injury: a retrospective multicenter study in Korea - Sukdong Yoo; Min Hyun Cho; Hee Sun Baek; Ji Yeon Song; Hye Sun Lee; Eun Mi Yang; Kee Hwan Yoo; Su Jin Kim; Jae Il Shin; Keum Hwa Lee; Tae-Sun Ha; Kyung Mi Jang; et al. (The Korean Society of Nephrology, 2021)
Background The clinical features of pediatric rhabdomyolysis differ from those of the adults with rhabdomyolysis; however, multicenter studies are lacking. This study aimed to investigate the characteristics of pediatric rhabdomyolysis and reveal the risk factors for acute kidney injury (AKI) in such cases. Methods This retrospective study analyzed the medical records of children and adolescents diagnosed with rhabdomyolysis at 23 hospitals in South Korea between January 2007 and December 2016. Results Among 880 patients, those aged 3 to 5 years old composed the largest subgroup (19.4%), and all age subgroups were predominantly male. The incidence of AKI was 11.3%. Neurological disorders (53.6%) and infection (39.0%) were the most common underlying disorder and cause of rhabdomyolysis, respectively. The median age at diagnosis in the AKI subgroup was older than that in the non-AKI subgroup (12.2 years vs. 8.0 years). There were no significant differences in body mass index, myalgia, dark-colored urine, or the number of causal factors between the two AKI-status subgroups. The multivariate logistic regression model indicated that the following factors were independently associated with AKI: multiorgan failure, presence of an underlying disorder, strong positive urine occult blood, increased aspartate aminotransferase and uric acid levels, and reduced calcium levels. Conclusions Our study revealed characteristic clinical and laboratory features of rhabdomyolysis in a Korean pediatric population and highlighted the risk factors for AKI in these cases. Our findings will contribute to a greater understanding of pediatric rhabdomyolysis and may enable early intervention against rhabdomyolysis-induced AKI.